MOLECULAR CHARACTERIZATION AND PHYLOGENETIC ANALYSIS OF AVIAN POX VIRUS ISOLATED FROM PET BIRDS AND COMMERCIAL FLOCKS, IN IRAN - Arash Ghalyanchilangeroudi; Hossein Hosseini; Rima Morshed (Slovenian Veterinary Research, 2018)
Avian pox (AP) is a viral disease with a wide host range. The aim of the study was molecular identification and characterization of field isolated pox virus from pet birds and commercial flocks in Iran, by polymerase chain reaction (PCR). Scab materials of skin and mucosal lesions were collected from five clinically affected cases. PCR was used to amplify a 578 bp fragment of the poxvirus 4b core protein. In order to determine the genetic relationships among the viruses, this conserved poxvirus genetic region was sequenced and analyzed. The Iranian Avipoxvirus isolates in this study grouped in clade A1 (commercial chicken and turkey flocks) and B1 (canary). Further studies on a larger scale need to be developed to have a better understanding of the molecular characterization of the Iranian APV strains.